2011
DOI: 10.1002/clen.201000373
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Quality in the Elbe River at Low Water Conditions Based on Factor Analysis

Abstract: An assessment of water quality measurements during a long-lasting low water period in the Elbe River is presented. Weekly samples were taken from May to December 2003 at a sampling site in the middle part of the Elbe River. For multivariate data analysis, 34 parameters of 46 samplings were considered. As a result of this analysis, 78% of the variance of the data set is explained by five factors. They can be assigned to the following latent variables: season (37.5%) > tributaries (12.7%) > re-suspension (10.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Sulfate (SO 2− 4 ) and chloride (Cl − ) were analysed by suppressed conductivity using an ICS-3000 ion chromatography system (Dionex, Idstein, Germany) and automatically generated potassium hydroxide eluent. Concentrations of Ca, Mg, Na, K, Al, Fe, and Mn were determined by optical emission spectroscopy with inductively coupled plasma (ICP-OES, Perkin-Elmer, OPTIMA 3000, Germany) (Baborowski, et al, 2011). Acidity and alkalinity were measured by an automatic titrator (Metrohm, Germany).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Sulfate (SO 2− 4 ) and chloride (Cl − ) were analysed by suppressed conductivity using an ICS-3000 ion chromatography system (Dionex, Idstein, Germany) and automatically generated potassium hydroxide eluent. Concentrations of Ca, Mg, Na, K, Al, Fe, and Mn were determined by optical emission spectroscopy with inductively coupled plasma (ICP-OES, Perkin-Elmer, OPTIMA 3000, Germany) (Baborowski, et al, 2011). Acidity and alkalinity were measured by an automatic titrator (Metrohm, Germany).…”
Section: Data Availabilitymentioning
confidence: 99%
“…This improvement is probably due to increased water levels in lakes due to snowmelt and precipitation [42]. Another study also showed the effect of seasonal fluctuations on the river water quality [43].…”
Section: Cluster Analysismentioning
confidence: 99%
“…The presence of CHL-a can be enhanced by higher amounts of TP; thus PC-3 can also be considered as an indicator of biological activities like PC-2. Baborowski et al [43] observed that concentration of CHL-a is directly related to the development of phytoplankton using factor analysis technique. The potential source of Ca is the sedimentary bedrock.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…For each principal component, component loadings indicate the correlation between the original variables and the newly formed components, which can be used to determine the relative importance of a parameter compared to others in a PC rather than the importance of the component itself [54][55][56]. From Tab.…”
Section: Parameters Related To the Variation Of Water Quality Betweenmentioning
confidence: 99%